METODE LOGIKA FUZZY TSUKAMOTO DALAM SISTEM PENGAMBILAN KEPUTUSAN PENERIMAAN BEASISWA - Maryaningsih, Maryaningsih; Siswanto, Siswanto; Mesterjon, Mesterjon (Jurnal Media Infotama, 2013)
The decision making process in determining the recipients of problems mainly lie in subjectivity, in which there are some students who have the ability or the value is not much different. Thus it is necessary to build a support system in making decisions that can be used to simplify the determination of who is eligible for the scholarship. The system is supported by Tsukamoto Fuzzy Logic method which is based on data and norms of human resources with the criteria specified by the donor. The result of this process is the weight of student assessment is the basis on which decisions recipients. Software is created by using Microsoft Access 2007 and Visual Basic 6.0 to Microsoft as a tool with these applications can help the scholarship awardees in the screening process accurately and quickly.